OBSERVASI PENGAMATAN DI KAWASAN EKOSISTEM ESSENSIAL (KEE) UJUNGPANGKAH KABUPATEN GRESIK TERKAIT DENGAN NELAYAN DAN ALAT PENANGKAPAN IKAN - Masyhudi Masyhudi; Hanifan Nanda; Yusria Latifa; Irvan Gunawan (Universitas Muhammadiyah Gresik, 2021)
The Essential Ecosystem Area (KEE) of Pangkah Wetan Village, Ujung Pangkah District, Gresik Regency is an area formed at the mouth of the Bengawan Solo River. This area has an important value as a very wide and diverse mangrove ecosystem. In addition, this area also has a fairly high fishery potential. The economic dominance of the surrounding community is generated from the results of ponds, tourism and capture fisheries products, many of the surrounding communities work as farmers and fishermen. This study aims to (1) determine the types of fishing gear operated, (2) determine the types of fish caught. To achieve the objectives of this study, it was conducted by means of observation and survey of respondents around the Ujung Pangkah KEE, Pangkah Wetan Village. The results showed that in Pangkah Wetan Village the fishermen were divided into 7 groups of fishermen. This was distinguished from the type of boat and fishing gear used, the groups were crab group, drag group, net group, anco group, penggaes group, frog net group and group messenger. From the 7 groups, several types of fish were caught, including milkfish, laosan, mullet, crab, shrimp, gamak, snapper, and crab.